Pengaruh Good Corporate Governance terhadap Manajemen Laba pada Perusahaan dalam Notasi Khusus yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2018 – 2020 - Dzikrina Indriani; Chasan Azari; Setya Prihatiningtyas (Journal Of Accounting and Business, 2022)
Corporate governance can be interpreted as a corporate control mechanism where the mechanism focuses on financial management managed by financial managers in order to gain profitability in order to attract investors. This study aims to determine the effect of Good Corporate Governance (GCG) on earnings management in companies listed on the Indonesia Stock Exchange for the period 2018 – 2020, simultaneously. The data analysis method in this study used a simple linear regression model. Based on the results of the study, it shows that the variable of Good Corporate Governance has a significant effect on earnings management simultaneously.